(untitled) (Conferencea, 2022)
Today with the increasing number of wireless LANs, the demand for high data rates with an improved level of security is a huge demand. This research involves analysis and comparison of different IEEE802.11 standards and the security protocols using practical application scenarios. The main purpose of this work is to reflect the collected data measurements of IEEE 802.11g and IEEE802.11n standards in terms of bandwidth and data throughput. IEEE 802.11 is a protocol family that enable wireless communication by the means of AP (Access Point) or ad-hoc (Sangolli.S, Jayavignesh.T, 2015). The results clearly showed us that there is a noticeable difference between the actual throughput and the expected bandwidth and in practice the maximum data rate can only reach one third of the channel bit rate. This research will be of a great importance to researchers and also specialists for further development of WLAN operations in the future.